Integration of Fintech and Islamic Banking in Indonesia: Opportunities and Challenges - Mufti Afif; Andriani Samsuri (Universitas Muhammadiyah Magelang, 2022)
This paper is intended to analyze the opportunities and challenges of collaboration between the fintech industry and Islamic banking in Indonesia. This research is a descriptive qualitative study of literature review, by collecting information, identifying problems, and making evaluations. Data analysis using SWOT platform. The results of the study show there are opportunities, that the digitalization system in Indonesia is developing very quickly, so that it can be used as a means to improve services in Islamic banking. In this way, Islamic Bank services can reach remote areas, reduce costs, and increase the Islamic financial inclusion. The biggest challenge is related to regulators. The Indonesian, which is predominantly Muslim, requires definite sharia rules regarding services at several types of fintech, which until now do not have a sharia fatwa. Fintech will continue to develop, or contrary, Islamic fintech may sink and be replaced by other technological innovations.